(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The Renin–Angiotensin System (RAS) may contribute to proteinuria and progression of Diabetic Nephropathy (DN). Vitamin D therapy is found to have an inhibitory effect on the RAS. The aim of this study was to evaluate the effects of Vitamin D therapy in retarding the progression of DN. Materials and methods: This was a single-center, double-blind, randomized placebo-controlled study conducted in Chittagong Medical College Hospital from June 2018 to May 2019. Thirty four eligible participants were randomly allocated to two groups in a 1:1 ratio. Experimental group received oral calcitriol 0.25 micro gm once daily and control group received placebo along with standard of therapy. Patients were evaluated at baseline and subsequently at 4th, 8th and 12th weeks for outcome evaluation. Serum creatinine, eGFR, uACR levels, serum calcium level, serum phosphate level, serum PTH level and any other tests as needed were done. Per protocol principle were used to analyze the data. Results: Fifteen patients from each group were finally completed the study and included in analysis. After 12 weeks, uACR was decreased in experimental group (Median 40.8 µg/mg) and increased in control group (Median 43.3 µg/mg). It were highly significant in comparison between two groups (p<0.001). Significant decrease in serum creatinine and increase in the eGFR was observed in the treatment group while in the control group, serum creatinine was increased and eGFR was decreased and it were highly significant (p<0.001 & p=0.001 respectively). In other parameters (SBP, serum phosphate and PTH) were significant in comparison between two groups at the end of study. But, changes of parameters like DBP, serum albumin and calcium were similar between two groups after 12 weeks. Conclusion: Vitamin D oral calcitriol 0.25 micro gm capsule given daily for 12 weeks reduces urine albumin and serum creatinine levels in patients with DN. JCMCTA 2024 ; 35 (2) : 105-111